Unusual presentation of fibrolamellar carcinoma: A rare case report - Chaudhari, Sachin; Rastogi, Archana; Taneja, Kanika; Thapar, Shalini; Agrawal, Nikhil (Indian Journal of Case Reports, 2017)
Fibrolamellar hepatocellular carcinoma (fHCC) is a distinct type of first time used hence- hepatocellular carcinoma affecting particularly young patient with no gender predilection. However, there is increasing evidence of occurrence of this tumor in elderly patients also. Abdominal imaging with pre-operative biopsy provides accurate diagnosis. However, in difficult situations, CD68, cytokeratin 7, HepPar1, etc., immunohistochemical stains provide accurate diagnosis to differentiate this condition from other malignancies. Hereby, we present a case of fHCC in a 55-year-old female with equivocal imaging features and diagnosis was made by histopathology aided by immunohistochemistry.